Development Environments and Factors of Subsidence Dolines - Márton Veress (Geosciences, 2021)
This study describes the development environments of subsidence dolines based on literary data (development environments create favorable conditions for the local denudation of superficial deposit and thus, for the development of depressions). Development environments are the inclination of the bearing surface, the secondary porosity of the bedrock, the characteristics of the cover, water influx into the cover, karstwater and groundwater, melting permafrost, and anthropogenic activity. These may become optimal when controlled by various geological, geomorphological, and climatic factors. Development environments may be qualitative (there is doline development in case of its presence) and quantitative (doline development occurs in case of suitable quantitative values). The development environment groups of subsidence dolines are environment groups independent of water level, environment groups dependent on water level, and anthropogenic environment groups. In the case of an environment group independent of water level, surface morphology, cover characteristics, geomorphic evolution, and water supply are determining, while in case of an environment group dependent of water level, subsurface water level and its fluctuations and the characteristics of rainfalls interrupting dry seasons are crucial. Anthropogenic impacts mainly affect doline development through water balance.